ACHIEVEMENT OF ORGANIZATIONAL PERFORMANCE: THE ROLE OF JOBMOTIVATION, JOB SATISFACTION, AND JOB PRODUCTIVITY - Hidayat, Syamsul; Hadiyuswara, Iyus Guntur; Atomy, Sri; Surani, Dewi (Jurnal Manajemen Bisnis, 2019)
This study entitled Analysis of Influence of Job Motivation and Job Satisfaction to Organizational Performance with Job Productivity as an intervening variable (Empirical Study at BPJS Kesehatan Branch Serang). Methods of data collection used random sampling methods, and the respondents were all employees totaling 46 people. Data was collected using a questionnaire method to give a list of questions directly to the respondents. Data analysis techniques in this study used path analysis, which was operated by SmartPLS. The results showed a positive relationship between job satisfaction and organizational performance and a positive relationship between job satisfaction and job productivity. The path analysis found that job motivation and job satisfaction do not affect organizational performance through productivity. Thus, it can be concluded that productivity does not become an intervening variable between job motivation and job satisfaction.